Electrical, Mechanical, and Hermetic Properties of Low-Temperature, Plasma Activated Direct Silicon Bonded Joints. (15th May 2015) - Schjølberg-Henriksen, K.; Malik, N.; Gundersen, E. V.; Christiansen, O. R.; Imenes, K.; Fournel, F.; Moe, S.
Abstract : The electrical, mechanical, and hermeticity properties of low-temperature, plasma activated direct silicon bonds were investigated. On individual dies with a bonding area ranging from 1–4 mm 2, the bonded interface was found to have a capacitance ranging from 2.62 pF/mm 2 –2.89 pF/mm 2 at 1 kHz. Linear I-V curves showed ohmic behavior without hysteresis. A resistance around 2.2 Ω and a current density of 1.1 × 10 4 A/m 2 was measured at DC. We speculate that the capacitive and resistive responses are related to traps that are formed during the plasma activation process. The applied bonding process resulted in hermetic sealing with 100% yield on 2 × 481 dies. The maximum leak rate of the seals was 2.4 × 10 −11 mbar⋅l⋅s −1, but could be significantly lower. No gross leaks were observed following a steady-state life test, a thermal shock test, and a moisture resistance test applied on 100 dies.